2017
DOI: 10.1080/13651501.2017.1324036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of depression symptoms between primary depression and secondary-to-schizophrenia depression

Abstract: It is clinically hard to differentiate primary from secondary-to-schizophrenia depression, especially in the absence of obvious psychotic symptoms. However, the classical symptoms of depression like subjective depressed mood, anhedonia, reduced energy and pathological guilt are more prominent in the primary depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
2
19
0
3
Order By: Relevance
“…It is challenging to distinguish between primary negative symptoms, secondary negative symptoms due to depression, and depression without negative symptoms [4,33,35,41]. Depression is an important co-occurring syndrome in schizophrenia, presenting with substantial anhedonia, reduced goaldirected behavior, and social withdrawal, that is, symptoms that are in overlap with negative symptoms [4,35,[228][229][230][231]. However, according to a meta-analysis conducted by Lako and colleagues (2012) [232] and three more recent studies [233][234][235], the differential diagnosis might improve using the Calgary Depression Scale for Schizophrenia [236], which is considered the best assessment instrument for depressive symptoms in subjects with schizophrenia compared to other scales such as the PANSS, the BPRS, the Hamilton Rating Scale for Depression, the Montgomery-Asberg Depression Rating Scale, the Beck Depression Inventory, as well as the Quick Inventory of Depressive Symptomatology-Self-Report (Table e8).…”
Section: Recognition Of Secondary Negative Symptoms Due To Depressionmentioning
confidence: 99%
“…It is challenging to distinguish between primary negative symptoms, secondary negative symptoms due to depression, and depression without negative symptoms [4,33,35,41]. Depression is an important co-occurring syndrome in schizophrenia, presenting with substantial anhedonia, reduced goaldirected behavior, and social withdrawal, that is, symptoms that are in overlap with negative symptoms [4,35,[228][229][230][231]. However, according to a meta-analysis conducted by Lako and colleagues (2012) [232] and three more recent studies [233][234][235], the differential diagnosis might improve using the Calgary Depression Scale for Schizophrenia [236], which is considered the best assessment instrument for depressive symptoms in subjects with schizophrenia compared to other scales such as the PANSS, the BPRS, the Hamilton Rating Scale for Depression, the Montgomery-Asberg Depression Rating Scale, the Beck Depression Inventory, as well as the Quick Inventory of Depressive Symptomatology-Self-Report (Table e8).…”
Section: Recognition Of Secondary Negative Symptoms Due To Depressionmentioning
confidence: 99%
“…It can also cause physical problems and decrease the person's ability to function in routine activities [7]. The severity of symptoms varies, from feelings of sadness to anxiety or restlessness, loss of interest, sleep disturbances, reduced appetite, and fatigue [8]. Social isolation and distancing can disrupt routines and create fear and anxiety, especially among those with mental health problems [4].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic evidence showed that the prevalence of depression is high among people with schizophrenia as compared with the general population [5, 6]. The reported prevalence estimates of depression and depressive symptoms among people with schizophrenia range between 7 to 65% depending on the studies [5, 710].…”
Section: Introductionmentioning
confidence: 99%